2000
DOI: 10.1103/physrevlett.85.3716
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of the Washboard Noise of a Driven Vortex Lattice in a High-Temperature Superconductor,Bi2Sr2CaCu

Abstract: We studied the conduction noise spectrum in the vortex state of a high-temperature superconductor, Bi(2)Sr(2)CaCu(2)O(y), subject to a uniform driving force. Two characteristic features, a broad-band noise (BBN) and a narrow-band noise (NBN), were observed in the vortex-solid phase. The origin of the large BBN was determined to be plastic motion of the vortices, whereas the NBN was found to originate from the washboard modulation of the translational velocity of the driven vortices. We believe this to be the f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
52
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 35 publications
7
52
0
Order By: Relevance
“…This is quite different from the time scale of the NBN observed in the conduction noise, which was the washboard noise [18].…”
Section: Narrow-band Noisementioning
confidence: 44%
“…This is quite different from the time scale of the NBN observed in the conduction noise, which was the washboard noise [18].…”
Section: Narrow-band Noisementioning
confidence: 44%
“…In the moving smectic, the short range of the position correlation along the flow direction totally destroys the temporal order of the moving vortices. To the best of our knowledge, the washboard noise, observed recently in both conventional 7 and high-T c superconductors, 8 has never been reported in numerical simulations except in 2D at zero temperature. 21 We believe this to be the first observation of the washboard velocity modulation of driven vortex matter in 3D numerical simulations.…”
mentioning
confidence: 64%
“…74.60.Ge,74.50.+r,74.40.+k Dynamical properties of current driven vortex matter 1,2,3 interacting with random pinning potentials in type II superconductors have attracted considerable attention both experimentally 4,5,6,7,8 and theoretically. 9,10,11,12 A better understanding of various nonequilbrium phases and phase transitions is essential for explaining the nonlinear current-voltage (I-V) characteristics observed in experiments conducting on samples in an external magnetic field, 4,13 which is known as the first evidence of the first-order vortex lattice melting.…”
mentioning
confidence: 99%
“…For large driving force, vortices move rather uniformly, with a periodic modulation of velocity suffered from the pinning centers (washboard oscillation). This washboard oscillation of driven vortices was observed experimentally [9,10,11]. On the other hand, close to the critical driving force (critical current density, j c ), vortices show a linear resistivity at finite temperatures [12].…”
Section: Introductionmentioning
confidence: 85%
“…Even restricting our interest on the moving state, various styles of motion have been proposed, indeed, for driven vortices, such as plastic motion [19], moving Bragg glass [17], and smectic motion [16]. We investigated the noise generated by the vortex motion by measuring the local density noise [24,25] and the velocity noise [11] simultaneously [26]. Together with the resistivity data and the ac-dc interference data, we found that the vortices first showed the plastic flow.…”
Section: Introductionmentioning
confidence: 99%